Traumatic Experiences, Perceived Discrimination, and Psychological Distress Among Members of Various Socially Marginalized Groups - Matheson, Kimberly; Foster, Mindi D.; Bombay, Amy; McQuaid, Robyn J.; Anisman, Hymie (Frontiers in Psychology, 2019)
Perceived discrimination has consistently been shown to be associated with diminished mental health, but the psychological processes underlying this link are less well understood. The present series of four studies assessed the role of a history traumatic events in generating a proliferation of discrimination stressors and threat appraisals, which in turn predict psychological distress (depressive and posttraumatic stress symptoms) (mediation model), or whether prior traumatic events sensitize group members, such that when they encounter discrimination, the link to stress-related symptoms is heightened (moderation model). Each of the studies assessed a different marginalized group in Canada, including Indigenous peoples, Blacks, Jews, and a diverse sample of women. Participants completed measures assessing history of traumatic events, perceived explicit and ambiguous discrimination, discrimination threat appraisals, and symptoms of depression and posttraumatic stress. The four populations varied in their experiences, with Indigenous peoples encountering the highest levels of trauma, discrimination, and psychological distress symptoms. A mediated model was evident among Indigenous peoples and women, possibly reflecting the role of systemic processes that engender discrimination when traumatic events are experienced. There was evidence for a moderating role of a history of traumatic events on the relations between discrimination and depressive symptoms among Jewish and Black participants. Although the hypothesized synergistic effects of traumatic experiences were noted when assessing the relation between perceived discrimination and depressive symptoms among Jews, the presence of trauma blunted these relations among Blacks. The results suggest that trauma-informed approaches to addressing stress-related processes and psychological outcomes need to consider the unique social context of members of various socially marginalized groups.